In Situ Catalytic Pyrolysis of Miscanthus Over Modified SBA-15 Catalysts Using Py-GC/MS - Lee, Eun Hwa; Jeon, Mi-Jin; Jeon, Jong-Ki; Suh, Dong Jin; Park, Sung Hoon; Seo, Bora; Joo, Sang Hoon; Park, Young-Kwon (AMER SCIENTIFIC PUBLISHERS, 2014)
Various SBA-15-based catalysts, Si-SBA-15, Pt/Si-SBA-15, Al-SBA-15, and Pt/Al-SBA-15, were applied to the catalytic pyrolysis of miscanthus. Pt nanoparticles with three different sizes, 1.7 nm, 2.9 nm, and 7.1 nm, were used to synthesize Pt/Si-SBA-15 and Pt/Al-SBA-15. Pyrolysis-gas chromatography/mass spectrometry was used for the pyrolysis experiments. The catalysts were characterized by X-ray diffraction patterns, transmittance electron microscopy, N-2 adsorption-desorption, and Brunaure-Emmett-Teller surface area. The product species distribution of pyrolysis of miscanthus was significantly affected by the acid property of the catalyst and the presence of Pt. In particular, Pt/Al-SBA-15, which has both acid sites and Pt, changed the product species distribution to the largest extent; the main products were phenolics and furans. The effect of Pt particle size on the species distribution of pyrolysis product was negligible.
Keywords: WASTE MANDARIN RESIDUE; BIOMASS; SILICA; CONVERSION; ALUMINA; EUROPE